Autonomous motivation, social support, and physical activity in school children: moderating effects of school-based rope skipping sports participation - Qi, Yufei; Yin, Yao; Wang, Xuyang; Zou, Yong; Liu, Bo (Frontiers in Public Health, 2024)
Purpose: Recent studies have shown that physical activity (PA) levels are low among children and adolescents globally. In order to reverse this trend, PA interventions are increasingly favoured. The school setting is the ideal place to address the issues that many children face. The purpose of this study was to (a) The primary focus of this study is to delve into the mediating role played by school-based rope skipping sports participation (SRSP) in the connection between social support and moderate to high-intensity physical activity (MVPA) among school children. (b) Additionally, this research aims to examine the moderating effect of within this pathway. Methods: We conducted a survey involving 721 adolescents residing in Changsha City. The participants' ages ranged from 8 to 12 years, with an average age of 9.84±1.535 years. Out of these participants, 406 were boys, and 315 were girls. To assess variables such as social support and autonomous motivation, we employed standardized measurement scales. Subsequently, we analyzed the collected data using various statistical methods, including independent s-amples t-tests, bivariate correlation analysis, descriptive statistical analysis, structural equation modeling (SEM), and the Johnson-Neyman method. Results: An independent samples t-test revealed a statistically significant difference in MVPA between genders (P=0.003 < 0.05), with boys exhibiting a higher level of engagement in MVPA compared to girls; Correlation analysis revealed significant positive associations among several key variables. Specifically, social support demonstrated a noteworthy positive correlation with autonomous motivation (r = 0.331, P < 0.01) as well as school children's engagement in MVPA (r = 0.308, P < 0.01). Moreover, autonomous motivation displayed a significant positive correlation with school children's involvement in MVPA (r = 0.459, P < 0.01). The moderating analysis revealed a significant influence of the interaction between increased participation in and social support on school children's engagement in MVPA. Conclusions: Social support and autonomy support have been proven effective in enhancing school children's engagement in MVPA. They exert their influence indirectly by fostering autonomous motivation. Notably, robust social support can significantly benefit MVPA school children with high activity requirements, particularly those regularly engaged in MVPA during the school day.